Aging-related alterations in eNOS and nNOS responsiveness and smooth muscle reactivity of murine basilar arteries are modulated by apocynin and phosphorylation of myosin phosphatase targeting subunit-1. Issue 3 (March 2017) - Lubomirov, Lubomir T; Papadopoulos, Symeon; Pütz, Sandra; Welter, Johannes; Klöckener, Tim; Weckmüller, Kathrin; Ardestani, Mostafa A; Filipova, Dilyana; Metzler, Doris; Metzner, Harald; Staszewski, Jürgen; Zittrich, Stefan; et al.
Aging causes major alterations of all components of the neurovascular unit and compromises brain blood supply. Here, we tested how aging affects vascular reactivity in basilar arteries from young (<10 weeks; y-BA), old (>22 months; o-BA) and old (>22 months) heterozygous MYPT1-T-696A/+ knock-in mice. In isometrically mounted o-BA, media thickness was increased by ∼10% while the passive length tension relations were not altered. Endothelial denudation or pan-NOS inhibition (100 µmol/L L-NAME) increased the basal tone by 11% in y-BA and 23% in o-BA, while inhibition of nNOS (1 µmol/L L-NPA) induced ∼10% increase in both ages. eNOS expression was ∼2-fold higher in o-BA. In o-BA, U46619-induced force was augmented (pEC50 ∼6.9 vs. pEC50 ∼6.5) while responsiveness to DEA-NONOate, electrical field stimulation or nicotine was decreased. Basal phosphorylation of MLC20 -S19 and MYPT1-T-853 was higher in o-BA and was reversed by apocynin. Furthermore, permeabilized o-BA showed enhanced Ca 2+ -sensitivity. Old T-696A/+ BA displayed a reduced phosphorylation of MYPT1-T696 and MLC20, a lower basal tone in response to L-NAME and a reduced eNOS expression. The results indicate that the vascular hypercontractility found in o-BA is mediated by inhibition of MLCP and is partially compensated by an upregulation of endothelial NO release.